Underwater Crawling Robot With Hydraulic Soft Actuators - Tan, Qinlin; Chen, Yishan; Liu, Jianhui; Zou, Kehan; Yi, Juan; Liu, Sicong; Wang, Zheng (Frontiers in Robotics and AI, 2021)
Benthic operation plays a vital role in underwater applications, presenting special challenges for underwater robots with the accumulated sediments covering the seabed. Crawling robots generally present lower disturbances than turbine-based underwater vehicles, while also excel in carrying payloads. However, motor-based robotic joints would still require extra protection against benthic sediments. Soft robots offer natural sealing against environmental elements, but their limited rigidity and trajectory precision hinder their capability to generate precise gaits for low-disturbance underwater locomotion. In this work, we propose a novel underwater crawling robot with innovative rigid-reinforced soft actuator joints. With the hydraulic soft actuators strengthened by their rigid linkage structures, the resulting soft-rigid hybrid legs could achieve precision, strength, and compliance simultaneously. A prototype crawling robot was developed based on the hybrid leg design, with all necessary components contained within its body. The untethered crawling robot could achieve over 5 times payload capability while presenting minimal disturbance to benthic sediments.